Autosomal dominant mitochondrial membrane protein‐associated neurodegeneration (MPAN) - Allison Gregory; Mitesh Lotia; Suh Young Jeong; Rachel Fox; Dolly Zhen; Lynn Sanford; Jeff Hamada; Amir Jahic; Christian Beetz; Alison Freed; Manju A. Kurian; Thomas Cullup; et al. (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Mitochondrial membrane protein‐associated neurodegeneration (MPAN) is caused by pathogenic sequence variants in C19orf12. Autosomal recessive inheritance has been demonstrated. We present evidence of autosomal dominant MPAN and propose a mechanism to explain these cases. Methods Two large families with apparently dominant MPAN were investigated; additional singleton cases of MPAN were identified. Gene sequencing and multiplex ligation‐dependent probe amplification were used to characterize the causative sequence variants in C19orf12. Post‐mortem brain from affected subjects was examined. Results In two multi‐generation non‐consanguineous families, we identified different nonsense sequence variations in C19orf12 that segregate with the MPAN phenotype. Brain pathology was similar to that of autosomal recessive MPAN. We additionally identified a preponderance of cases with single heterozygous pathogenic sequence variants, including two with de novo changes. Conclusions We present three lines of clinical evidence to demonstrate that MPAN can manifest as a result of only one pathogenic C19orf12 sequence variant. We propose that truncated C19orf12 proteins, resulting from nonsense variants in the final exon in our autosomal dominant cohort, impair function of the normal protein produced from the non‐mutated allele via a dominant negative mechanism and cause loss of function. These findings impact the clinical diagnostic evaluation and counseling.